PENDEKATAN SEKURITISASI TERHADAP KRISIS PENGUNGSI MYANMAR: ANTARA KEAMANAN WILAYAH DAN TANGGUNG JAWAB KEMANUSIAAN THAILAND - Ramadhani, Riva (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2025)
The Myanmar refugee crisis triggered by political conflict and violence in Myanmar has created major challenges for Thailand, especially in maintaining a balance between border security and humanitarian obligations. This research analyses how the Myanmar refugee crisis affects security dynamics on the Thai-Myanmar border as well as the strategies implemented by Thailand to manage border security while considering refugee protection. Using a desk study approach, this research integrates various academic sources to understand the complexity of this issue. The findings show that Thailand tends to prioritise national security through a securitisation approach, which often limits refugees' access to protection and humanitarian assistance. However, pressure from the international community and humanitarian organisations is pushing Thailand to adopt a more balanced approach. This research contributes to the study of forced migration, regional security, and ASEAN policy by highlighting the dilemma between state sovereignty and humanitarian responsibility.